Biblical Eschatology from Creation to Consummation in Christ and Its Implications for the Church - Mawikere, Marde Christian Stenly; Hura, Sudiria (Sekolah Tinggi Teologi Simpson Ungaran, 2026)
This article examines biblical eschatology as a coherent theological metanarrative unfolding from creation to consummation in Christ, in whom all things hold together (Colossians 1:17). Eschatology is approached not as a speculative doctrine concerned primarily with future events, but as a present and ongoing reality grounded in the redemptive work and restorative reign of Christ. Through a qualitative theological methodology, employing canonical hermeneutics and lexical analysis of the term ἔσχατος, the study traces the eschatological trajectory of Scripture as it coheres around the person and work of Christ. This trajectory encompasses the original act of creation, its distortion through sin, the inauguration of restoration through the cross and resurrection, and its ultimate consummation in the new creation. Particular attention is given to Revelation 21, where the eschaton is depicted not merely as temporal finality but as the fulfillment of all things in Christ (παλινγενεσία), thereby revealing the divine purpose to restore creation through Him. This eschatological vision carries significant implications for the life and identity of God’s people as a whole. Those who are united in Christ are called to live in light of the inaugurated eschaton, embodying and enacting His restorative work in the world as a foretaste of the coming fullness. In this sense, the community of believers participates corporately in Christ’s renewing mission, manifesting even now the reality of the new creation toward which all history moves. The article thus offers an integrative framework that unites doctrine and discipleship, hope and mission, situating the vocation of God’s redeemed people within the telos of His redemptive purpose from creation to consummation in Christ.